Natural Polymorphisms Conferring Resistance to HCV Protease and Polymerase Inhibitors in Treatment-Naïve HIV/HCV Co-Infected Patients in China - Zhou, Kali (PLoS One, 2016)
BACKGROUND: The advent of direct-acting agents (DAAs) has improved treatment of HCV in HIV co-infection, but may be limited by primary drug resistance. This study reports the prevalence of natural polymorphisms conferring resistance to NS3/4A protease inhibitors and NS5B polymerase inhibitors in treatment-naïve HIV/HCV co-infected individuals in China. METHODS: Population based NS3/4A sequencing was completed for 778 treatment-naïve HIV/HCV co-infected patients from twelve provinces. NS3 sequences were amplified by nested PCR using in-house primers for genotypes 1–6. NS5B sequencing was completed for genotyping in 350 sequences. Resistance-associated variants (RAVs) were identified in positions associated with HCV resistance. RESULTS: Overall, 72.8% (566/778) of all HCV sequences had at least one RAV associated with HCV NS3/4A protease inhibitor resistance. Variants were found in 3.6% (7/193) of genotype 1, 100% (23/23) of genotype 2, 100% (237/237) of genotype 3 and 92% (299/325) of genotype 6 sequences. The Q80K variant was present in 98.4% of genotype 6a sequences. High-level RAVs were rare, occurring in only 0.8% of patients. 93% (64/69) patients with genotype 1b also carried the C316N variant associated with NS5B low-level resistance. CONCLUSIONS: The low frequency of high-level RAVs associated with primary HCV DAA resistance among all genotypes in HIV/HCV co-infected patients is encouraging. Further phenotypic studies and clinical research are needed.